A study on surgical management of undescended testis - M., Mallikarjuna; Dhotre, Mahesh; S., Shanmukhappa (International Journal of Research in Medical Sciences, 2018)
Background: Cryptorchidism which is synonymous with Undescended testes. It is one of the most common congenital anomalies found in children. The aim is to study the surgical management of undescended testis in relation to age, position, side, symptoms, complications and management of undescended testis. This study will present an overview of the current understanding of this challenging problem, mainly concentrating on surgical management. Methods: About 30 cases of undescended testis were included in the study, which were diagnosed with regards to age of presentation, clinical features, inclusion and exclusion criteria and relevant investigations like ultrasonography, diagnostic laparoscopy, CT whereever required. Cases were managed accordingly in the course of study and sampling of cases was taken from Bapuji Hospital and C.G. Hospital, Davangere during the study period. Results: Undescended testis was found more common on right side and most of them presented with the age group of 1-15 years with absence of testis in the scrotum being the most common complaint and hernia was found to be most commonly associated with undescended testis. Most common position of undescended testis was found to be intra-canalicular with most of them being palpable. The only one case had torsion and few of the cases had post operative complications like, wound infection haematoma. Open and laparoscopic orchidopexy can be used as most common procedure in early age group. Conclusions: Undescended testes is eminently treatable in today’s practice with the surgical procedures, an early diagnosis, informed counselling of parents and optimal surgical management offer optimised opportunities for successful placement and function of the testes which lessen the burden of complications.